Complexation of Cm(III) with fluoride in aqueous solution in the temperature range from 20 to 90 °C: a joint TRLFS and quantum chemical study - Skerencak-Frech, Andrej; Panak, Petra; Neck, Volker; Trumm, Michael; Schimmelpfennig, Bernd; Lindqvist-Reis, Patric; Klenze, Reinhardt; Fanghänel, Thomas (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2010)
The formation of hydrated CmF2+ and CmF2+ species in aqueous solutions are studied in the temperature range of 20−90 °C at different fluoride concentrations and at constant ionic strength as well as at constant fluoride concentration and different ionic strengths by means of time-resolved laser fluorescence spectroscopy (TRLFS). The molar fractions of the Cm3+ aqua ion, CmF2+, and CmF2+ species are determined by peak deconvolution of the emission spectra. An increase of the mono- and difluoro complexes is observed with increasing fluoride concentration and/or increasing temperature. Using the specific ion interaction theory (SIT), the thermodynamic stability constants log K10 (CmF2+) and log K20 (CmF2+) as well as the values of Δε1 and Δε2 are determined as a function of temperature. The log K10 values increase from 3.56 ± 0.07 to 3.98 ± 0.06 and the log K20 values increase from 2.20 ± 0.84 to 3.34 ± 0.21 with increasing temperature from 20 to 90 °C. The value of Δε1 determined at 25 °C is in good agreement with literature data and shows a negligible temperature dependency in the studied temperature range. The value of Δε2 also shows only a moderate variation in the studied temperature range. The thermodynamic standard state data (ΔrHm0, ΔrSm0, ΔrGm0) are determined from the temperature dependence of the equilibrium constants at Im = 0 using the integrated Van’t Hoff equation. The fluorescence lifetime of the 6D′7/2(Cm3+) state is found to be constant at 63 ± 5 μs with increasing fluoride concentration. A model based on density functional theory (DFT) calculations is introduced to account for the additional quenching occurring through the near second sphere waters in the [Cm(H2O)8F]2+(H2O)18 complex.